Hetero-nanotubos sob pressão hidrostática: um estudo ab initio - Pereira, Mauro Bogéa (2011)
In this work the electronic and structural properties of the hetero-nanotube bundles, composed of a CNT (6,0) encapsulated in a BNNT (14,0) (CNT (6,0)@BNNT (14,0)) and a BNNT (6,0) encapsulated in a CNT (14,0) (BNNT(6,0)@CNT (14,0)), under hydrostatic pressure. For this, we applied density functional theory and generalized gradient approximation to the exchange and correlation term, as implemented in SIESTA code. We observed that structural changes occur when pressure is applied. For the CNT(6,0)@BNNT(14,0) these changes begin when the pressure is close to 1,0 GPa for the outer tube, while for the inner tube the changes are observed around 10,0 GPa. In the case of BNNT(6,0)@CNT(14,0) the structure begins to be modified when the applied pressure is close to 3,0 GPa. The analysis of the band structure shown that the metallic character of the CNT(6,0)@BNNT(14,0) and the semiconductor character of the BNNT(6,0)@CNT(14,0) did not change when the pressure is applied.